2018
DOI: 10.1111/cei.13238
|View full text |Cite
|
Sign up to set email alerts
|

The immunopathogenesis of fibrosis in systemic sclerosis

Abstract: Summary Systemic sclerosis (SSc) is an idiopathic systemic autoimmune disease. It is characterized by a triad of hallmarks: immune dysfunction, fibrosis and vasculopathy. Immune dysfunction in SSc is characterized by the activation and recruitment of immune cells and the production of autoantibodies and cytokines. How immune abnormalities link the fibrosis and vasculopathy in SSc is poorly understood. A plethora of immune cell types are implicated in the immunopathogenesis of SSc, including T cells, B cells, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 132 publications
1
113
0
Order By: Relevance
“…It has been hypothesized that complexes of self-RNA and antimicrobial peptides can activate TLR3 [28]. Previous research has revealed that interferon-α2 increases the TLR3-induced production of interleukin-6 in dermal broblasts and overexpression of TLR3 in human skin, particularly in dermal broblasts present in the connective tissue of the dermis [25]. Our ndings can be used as a reference to further investigate the association between TLR3 and skin brosis.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…It has been hypothesized that complexes of self-RNA and antimicrobial peptides can activate TLR3 [28]. Previous research has revealed that interferon-α2 increases the TLR3-induced production of interleukin-6 in dermal broblasts and overexpression of TLR3 in human skin, particularly in dermal broblasts present in the connective tissue of the dermis [25]. Our ndings can be used as a reference to further investigate the association between TLR3 and skin brosis.…”
Section: Discussionmentioning
confidence: 64%
“…SSc affects the gastrointestinal tract, resulting in its progressive dysfunction. For example, small bowel disease occurs with smooth muscle atrophy, followed by the nal stage of muscle brosis [25]. As bowel movements change, the gut microbiota also changes, which may provoke an immune response, e.g., via TLR1, in patients with SSc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, while a beneficial impact of ibrutinib in autoimmune diseases like rheumatoid arthritis or SSc has been proposed from the very beginning, the transition to a clinical application in this field is incomplete [18]. In SSc, B cells are assumed to be important players in disease onset and progression [19,20]. B cells of patients with SSc show elevated expression levels of the regulatory surface molecule CD19, which reduces the threshold of BCR signaling, thereby importantly influencing B cell activation and survival [21].…”
Section: Discussionmentioning
confidence: 99%